(untitled) (Third Sector Social Economic Review, 2017)
There are 73.6 million mobile phone subscribers (Information and Communication Technologies Authority, 2015 4th Quarterly Report) and 35.2 million smartphone users in Turkey (http://www.statista.com, forecast for 2016) which has a population of 78.7 million (Turkish Statistical Institute, 31st December 2015), and every day steady growth continues in the smartphone market. In this respect, the increasing interest in smartphones has mobilized businesses. Businesses show outmost effort to ensure that customers are committed to their businesses and to sustain that their customers prefer them no matter what against their competitors. Therefore, it is of significant importance for businesses to investigate the features affecting the commitments of customers so that they can receive the expected commitment from their customers. In this regards, it is aimed at examining the theoretical background of a topic to which such a great deal of importance is attributed by practitioners and suggesting a model that will be compatible with the dynamics of Turkey. Based on this, the main focus of the study is to identify variables that can be effective in creating and maintaining customer loyalty. Within the scope of the research model of the study, data were collected through an online survey over the internet from the end-users of Samsung and Apple companies, which are the two largest key players in smartphone market in Turkey. 565 final surveys were subjected to analysis. It is envisaged that end-users who are satisfied with their products, have benefited from the quality offered by their smartphones based on the price they paid and time they spent, and who believe that the cost of switching to a new brand/operating system is high, will create customer loyalty towards the related brand.